(untitled) (Educação e Pesquisa, 2023)
Body image is defined as the mental representation of the body itself. Although there are studies that evaluated the body image of the population of university students in the physical education course, few sought to understand how it conceptualizes this construct. This research aimed to understand the perceptions about body image of a group of graduating students completing the degree course in physical education at a public university in Rio de Janeiro, focusing on how they construct and problematize the concept of body image and its applications in basic education. . This is a qualitative, descriptive and cross-sectional study, in which 31 university students, with a mean age of 24.6 years (SD=±3.4 years), participated in online focus groups and answered a sociodemographic questionnaire to the data collection. The sessions were recorded and transcribed for data analysis, and categorical content analysis by collection was used. Five categories emerged after the content analysis: (1) definitions and concepts about body image, (2) knowledge about when body image starts and when it stops, (3) influencing aspects of body image, (4) difference between body image body of men and women and (5) body image, formation and performance in basic education. It could be concluded that the participants understand body image based on a limited perspective, little based on the literature and based on their experiences, which can impact their future professional performance.